Designing a sport performance evaluation model in Khouzestan Province, Iran, with Interpretive Structural Modeling - Mazarei, E.; Heydarinejad, S.; Shafienia, P.; Zarra-Nezhad , M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Any sport organization intensively needs a performance evaluation system to ensure the desirability of its activities, particularly in dynamic and complicated environments. The objective of this study was to use interpretive structural modeling (ISM) to propose a performance evaluation model for the youth and sports offices in Khuzestan Province, Iran. This is a quantitative study of descriptive-analytical type. The statistical population consisted of 120 scientific and executive experts. 60 individuals were invited to participate, and finally, 30 individuals were selected as the final respondents by purposive sampling method. The data measurement tool was a researcher-made questionnaire. Its validity was confirmed by the experts. Descriptive and inferential statistics methods were used to analyze the data. MATLAB was employed to analyze the data concerning the interpretive structural model. The results showed that most of the strategies are in the linked area according to the analysis of the influence power and dependence (MICMAC Table). Moreover, the results of the strategy classification indicated that the most essential strategies were: strategies of sport preparation scheme, legislation, structural obstacles elimination, creation of the province sport strategic council, and strategic management approach.